Positive Ecological Interactions and the Success of Seagrass Restoration - Valdez, Stephanie R.; Zhang, Y. Stacy; van der Heide, Tjisse; Vanderklift, Mathew A.; Tarquinio, Flavia; Orth, Robert J.; Silliman, Brian R. (Frontiers in Marine Science, 2020)
Seagrasses are a valuable environmental resource. They provide a multitude of ecosystem services including nursery habitat, improved water quality, coastal protection, and carbon sequestration. However, seagrasses are in crisis as global coverage is declining at an accelerating rate. Recently, restoration has increased in popularity as a primary conservation action that may help re-establish degraded seagrass beds. With the elevation of restoration efforts as a conservation strategy, new methods that enhance restoration yields need to be explored. Terrestrially, incorporating positive species interactions and feedbacks into planting designs have proven beneficial to enhance restoration success at little additional cost. Decades of work in coastal plant ecosystems, including seagrasses, has shown that positive species relationships and feedbacks are critical for ecosystem stability, expansion, and recovery from disturbance. We reviewed the restoration literature on seagrasses and found, despite the critical role positive interactions play in marine plant systems, less than 8% of studies have tested for the beneficial effects of including positive interactions in seagrass restoration designs. Here we review the full suite of positive species interactions that have been documented in seagrass ecosystems, where they occur, and how they might be integrated into seagrass restoration. The few studies in marine plant communities that have explicitly incorporated positive species interactions and feedbacks have found an increase in plant growth with little additional resource investment. As oceans continue to change and stressors become more prevalent, pioneering restoration methods, such as harnessing positive feedbacks between species, will be key in rehabilitating populations of seagrasses.